Removable Partial Denture in Combination with a Milled Fixed Partial Prosthesis as Interim Restorations in Long-Term Treatment - Pellizzer, Eduardo Piza [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Verri, Fellippo Ramos [UNESP]; Falcon Antenucci, Rosse Mary; Goiato, Marcelo Coelho [UNESP] (Wiley-Blackwell, 2010)
Interim restorations are frequently used in prosthodontic treatments. Many complex situations require the combination of fixed and removable partial prostheses. An appropriate interim restoration design that accurately implements the treatment plan is necessary to prepare the oral cavity for the prostheses, and to contribute to the preservation and health of remaining natural teeth, bone support, and gingival tissues. This report describes a modified technique for construction of interim restorations with a combination of fixed and removable partial prostheses. The technique consists of the construction of a milled fixed prosthesis and removable partial denture with metallic framework for use during extensive treatment, improving masticatory function and esthetics and preserving the periodontal health of supporting structures. This interim restoration can also serve as a template for the definitive restoration, allowing patient and dentist to evaluate appearance and function and helping to ensure the success of the definitive restoration.
Keywords: Interim restorations; removable partial prostheses; fixed partial prostheses